J/ψ elliptic flow in Pb-Pb collisions at √sNN=2.76 TeV - Abbas, Ehab Gamal; Angelov, Venelin; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (Physical review letters, 2013)
We report on the first measurement of inclusive J/ψ elliptic flow v2 in heavy-ion collisions at the LHC. The measurement is performed with the ALICE detector in Pb-Pb collisions at √sNN=2.76 TeV in the rapidity range 2.5<y<4.0. The dependence of the J/ψ v2 on the collision centrality and on the J/ψ transverse momentum is studied in the range 0≤pT<10 GeV/c. For semicentral Pb-Pb collisions at √sNN=2.76 TeV, an indication of nonzero v2 is observed with a largest measured value of v2=0.116±0.046(stat)±0.029(syst) for J/ψ in the transverse momentum range 2≤pT<4 GeV/c. The elliptic flow measurement complements the previously reported ALICE results on the inclusive J/ψ nuclear modification factor and favors the scenario of a significant fraction of J/ψ production from charm quarks in a deconfined partonic phase.